The effect planting hole size and manure on vegetative growth of golden teak (Tectona grandis L.) - Didik Hariyono (Brawijaya University, 2018)
Cultivation of the golden teak (Tectona grandis L.) requires the planting hole size and appropriate use of manure. The size of planting hole provides plant growth, so that the plant can grow with optimum and appropriate use of manure to provide nutrients for the plants. . The aims of the study was to obtain an interaction between planting hole size and manure on vegetative growth phase of golden teak. Treatments tested in this study were with 4 treatment of planting hole size as the first factor and 3 levels of manure as the second factor. The twelve treatments were arranged in a factorial randomized block desiagn with three replicates. Variable measured plant height, number of leaves, and the flush changes to mature. The results showed that there were no interactions between the planting hole size and goat manure on early vegetative growth of golden teak plants. The planting hole size treatment showed significant effects on some variables height of plant, number of leaves and flush change to mature leaves. Manure treatment showed no significant effect for all variables. The observation variables that showed no significant differences height of plant, number of leaves and flush change to mature leaves.